Back silver paste for thin poly battery piece, preparation method of back silver paste and N-type TOPCon battery
By using high-active back silver paste in TOPCon batteries, using the complementary filling synergistic effect of the main and secondary silver powder and the high softening point glass phase, the problems of low silicon wafer thinning and poor efficiency gain effect of TOPCon batteries at high temperatures are solved, and good contact and high-efficiency conductivity are achieved at low sintering temperatures.
Patent Information
- Application Number
- CN202411935087.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-17
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-11
AI Technical Summary
During the preparation process, the silicon wafer is not thinned due to high temperature, which increases the cost of silicon material. In addition, it is difficult for conventional conductive paste to establish balanced open pressure and FF on thin poly batteries, and the efficiency gain effect is poor.
Using a highly active back silver paste, including 85 to 89 parts of main spherical silver powder, 1 to 5 parts of sub-spherical silver powder, 1.5 to 2 parts of lead-bismuth tellurium glass powder and 6 to 11 parts of organic binder, through the complementary filling synergy of main and secondary silver powder with significant differences in particle size, combined with the glass phase with high softening point, good contact between metal and metal and metal and battery silicon wafer at low sintering temperature is achieved.
The good contact between metal and metal and the battery silicon wafer is achieved at low sintering temperature, which reduces the series resistance of the battery cells, improves the conductivity, and ensures that the overall efficiency of the thinned battery cells is equal to or even better than that of conventional battery cells.
Smart Images

Figure CN119811739A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar cells, and in particular relates to a back silver paste for thin poly cell sheets and a preparation method thereof, and an N-type TOPCon cell. Background Art
[0002] Renewable energy represented by photovoltaics has gradually become the main force in achieving my country's energy structure optimization and "dual carbon" goals. Tunnel oxide passivating contact (TOPCon) cells with a higher efficiency limit (28.2% to 28.7%) have become a research focus. Their efficiency limit is higher than that of PERC cells (theoretical limit efficiency is 24.5%). They are the crystalline silicon cells closest to the theoretical limit efficiency of crystalline silicon solar cells (29.43%), and the efficiency of N-TOPCon cells has reached 26.10%. Against the background of rapid technological iteration in the photovoltaic industry, TOPCon cells take into account both cost and photoelectric conversion efficiency, and are the mainstream direction of future photovoltaic cell production technology development. TOPCon cells are subject to factors such as high temperature during the preparation process, and the degree of thinning of silicon wafers is not high, which means that when producing cells of the same power, TOPCon cells require more silicon material costs.
[0003] Therefore, the TOPCon process is currently trying to overcome the technical difficulties of large-size thin-film production.
[0004] Among them, the core of the TOPCon process is to prepare a tunneling oxide film on the surface of monocrystalline silicon. Due to the high reaction temperature of this process, the substrate wafer will be thermally deformed. The thinner the substrate monocrystalline silicon wafer is, the more obvious the thermal deformation will be, thereby reducing the battery efficiency. Therefore, it is necessary to propose a matching high-activity conductive paste. As an important raw material for crystalline silicon solar cells, the performance of conductive paste (for example, sintering activity, sintering temperature, etc.) has a decisive influence on the efficiency and production cost of crystalline silicon solar cells. When conventional conductive paste is used for thin poly cells, it is specifically manifested as the difficulty in establishing a balance between the opening voltage and FF, and the efficiency gain effect is poor. Therefore, the research on paste matching the cell thinning process is imminent. Summary of the invention
[0005] The present disclosure aims to solve at least one of the technical problems existing in the prior art, and provides a back silver paste suitable for thin poly battery sheets and a preparation method thereof, and an N-type TOPCon battery.
[0006] In one aspect of the present disclosure, there is provided a back silver paste suitable for a thin poly cell, the back silver paste comprising:
[0007] 85-89 parts by mass of primary spherical silver powder;
[0008] 1 to 5 parts by weight of para-spherical silver powder;
[0009] 1.5-2 parts by mass of lead bismuth telluride glass powder;
[0010] 6 to 11 parts by mass of an organic binder; wherein,
[0011] The D50 particle size of the primary spherical silver powder is 1.5 to 2 μm, and the D50 particle size of the secondary spherical silver powder is 2.5 to 3 μm.
[0012] Optionally, the specific surface area of the main spherical silver powder is 0.4 to 0.8 m 2 / g, tap density is 5~8g / cm 3 .
[0013] Optionally, the specific surface area of the para-spherical silver powder is 0.1 to 0.3 m 2 / g, tap density is 5~8g / cm 3 .
[0014] Optionally, the lead bismuth telluride glass powder comprises:
[0015] 25 to 35 parts by mass of a Pb-containing compound;
[0016] 13 to 25 parts by mass of a Bi-containing compound;
[0017] 25 to 45 parts by mass of a Te-containing compound;
[0018] 1 to 15 parts by mass of one or more of Si-containing compounds, Al-containing compounds, B-containing compounds, Ti-containing compounds, Na-containing compounds, Cu-containing compounds, and As-containing compounds.
[0019] Optionally, the organic binder includes:
[0020] 2 to 10 parts by weight of water-based resin;
[0021] 70 to 90 parts by weight of a solvent;
[0022] 1 to 3 parts by mass of a dispersant.
[0023] Optionally, the water-based resin is one or more of ethyl cellulose, acrylic resin, PVB resin, epoxy resin, and rosin resin; and / or,
[0024] The solvent is one or more of terpineol, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, and glycerol; and / or,
[0025] The dispersant is one or more of stearic acid, polyether, unsaturated fatty acid and phosphate.
[0026] Another aspect of the present disclosure provides a method for preparing the aforementioned back silver paste suitable for thin poly battery sheets, the method comprising:
[0027] The main spherical silver powder, the auxiliary spherical silver powder, the lead bismuth telluride glass and the organic binder are mixed to obtain a mixed material;
[0028] The mixed materials are centrifuged in sequence to obtain an intermediate slurry;
[0029] The intermediate slurry was mixed evenly using a three-roll grinder to obtain a back silver paste.
[0030] Optionally, the centrifugal treatment is performed at a speed of 500-600 rpm for a time of 2-7 min; and / or,
[0031] The intermediate slurry was rolled four times using a three-roll mill, and the rotation speed of the three-roll mill was 100-300 rpm during each rolling process.
[0032] Optionally, the fineness of the back silver paste is less than 15 μm.
[0033] In another aspect of the present disclosure, an N-type TOPCon battery is provided. The back side of the N-type TOPCon battery has a grid line, and the material of the grid line is the back side silver paste described above.
[0034] The present disclosure proposes a back silver paste suitable for thin poly cell sheets and a preparation method thereof, and an N-type TOPCon cell. The high-activity back silver paste comprises: 85 to 89 parts by mass of main spherical silver powder; 1 to 5 parts by mass of secondary spherical silver powder; 1.5 to 2 parts by mass of lead bismuth telluride glass powder; 6 to 11 parts by mass of organic binder; wherein the D50 particle size of the main spherical silver powder is 1.5 to 2 μm, and the D50 particle size of the secondary spherical silver powder is 2.5 to 3 μm. The present disclosure utilizes the complementary filling synergy of the main and secondary silver powders with significant differences in particle size, and cooperates with the glass phase with a high softening point to ensure good contact between metal and metal, and metal and battery silicon wafer on the poly layer thinned cell sheet at the lowest possible sintering temperature. In addition, the mutual cooperation of the small-particle main silver powder with the organic component and the inorganic component reduces the cell opening voltage loss easily caused by low temperature as much as possible, thereby ensuring that the overall efficiency of the thinned cell sheet can be equal to or even better than that of the conventional cell sheet. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The present invention is a flowchart of a method for preparing silver paste for the back side of a thin poly cell according to an embodiment of the present invention. DETAILED DESCRIPTION
[0036] In order to enable those skilled in the art to better understand the technical solution of the present disclosure, the present disclosure is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It should be understood that the specific embodiments described herein are only used to explain the present disclosure and are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.
[0037] In one aspect of the present disclosure, a high-activity back silver paste suitable for thin poly solar cells is provided, wherein the high-activity back silver paste comprises: 85 to 89 parts by mass of primary spherical silver powder; 1 to 5 parts by mass of secondary spherical silver powder; 1.5 to 2 parts by mass of lead bismuth telluride glass powder; and 6 to 11 parts by mass of an organic binder; wherein the D50 particle size of the primary spherical silver powder is 1.5 to 2 μm, and the D50 particle size of the secondary spherical silver powder is 2.5 to 3 μm.
[0038] It should be understood that compared with general cells, thin poly cells have higher requirements for paste performance. For example, they need to have appropriate sintering activity. If the sintering activity is too low, the contact performance between the conductive silver grid line and the silicon substrate will be poor. If the sintering activity is too high, it will burn through the oxide layer. The ideal state should be that the glass powder burns through the silicon nitride layer, the dissolved silver forms a good contact with the Poly layer, and does not corrode through the Poly layer, avoiding damage to the tunneling oxide layer. For another example, it is also necessary to have a suitable sintering temperature. If the sintering temperature is too high, the thermal deformation of the substrate single crystal silicon wafer will cause the efficiency of the cell to decrease, and the carrier recombination rate will also accelerate.
[0039] In this embodiment, silver powder with a smaller powder size is used as the main spherical silver powder, and silver powder with a larger powder size is used as the secondary spherical silver powder, and the secondary spherical silver powder is doped with the main spherical silver powder in a certain proportion, so that the slurry has suitable sintering activity, avoids burning through the tunneling oxide layer, and can obtain better contact performance between the conductive silver grid line and the silicon substrate; at the same time, the slurry also has a lower sintering temperature, which reduces the higher sintering temperature required to be reached during the metallization process of the battery cell during the sintering process, which to a certain extent helps to avoid the problem of reduced battery cell efficiency caused by thermal deformation of the substrate single crystal silicon wafer during the high-temperature sintering process under the battery cell thinning strategy. In addition, the reduction in sintering temperature also minimizes the carrier recombination rate and improves the carrier mobility.
[0040] It should be noted that in this embodiment, silver powders of different particle sizes are doped, and silver powders with smaller particle sizes and larger specific surface areas are selected as the main silver powders, which can greatly reduce the possibility of reverse leakage current and PN junction burnout, and maintain the opening voltage yield; at the same time, silver powders with larger particle sizes and smaller specific surface areas are selected as secondary silver powders, which can effectively improve the mutual filling ability of silver grains formed by the slurry during the sintering process, so that the slurry after sintering forms a more uniform and dense sintering film on the surface of the battery silicon wafer, reducing the series resistance of the battery cell and achieving better conductivity. In other words, by compounding small-particle silver powder and large-particle silver powder, the appropriate sintering degree required by the slurry for thin poly battery cells, high density after sintering, high opening voltage yield and FF, low series resistance, and low contact resistance performance balance can be achieved to match the thinning requirements of battery cells.
[0041] It should also be understood that parameters such as the content and particle size of large-particle silver powder and small-particle silver powder have an important influence on the performance of the slurry. Different contents and different particle size ranges will have different degrees of influence on the application of the slurry in the battery cell. Therefore, this embodiment further limits the parameters such as the content, particle size, specific surface area and tap density of the primary spherical silver powder and the secondary spherical silver powder to better meet the performance requirements of the slurry.
[0042] In some preferred embodiments, the content of the main spherical silver powder is preferably 85 parts by mass, 86 parts by mass, 87 parts by mass, 88 parts by mass, 89 parts by mass, etc., and the D50 particle size is preferably 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2μm, etc.
[0043] As a further preferred embodiment, the specific surface area of the main spherical silver powder is preferably 0.4 to 0.8 m 2 / g, for example, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, etc., and the tap density is preferably 5 to 8 g / cm 3 , for example, 5g / cm 3 , 6g / cm 3 , 7g / cm 3 , 8g / cm 3 wait.
[0044] In other preferred embodiments, the content of the para-spherical silver powder is preferably 1 mass part, 2 mass parts, 3 mass parts, 4 mass parts, 5 mass parts, etc., and the D50 particle size is preferably 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm, 3μm, etc.
[0045] As a further preferred embodiment, the specific surface area of the paraspherical silver powder is preferably 0.1 to 0.3 m 2 / g, for example, 0.1m 2 / g, 0.2m 2 / g, 0.3m 2 / g, etc., and the tap density is preferably 5 to 8 g / cm 3 , for example, 5g / cm 3 , 6g / cm 3 , 7g / cm 3 , 8g / cm 3 wait.
[0046] Furthermore, the lead bismuth telluride glass powder includes: 25 to 35 parts by mass of a Pb-containing compound; 13 to 25 parts by mass of a Bi-containing compound; 25 to 45 parts by mass of a Te-containing compound; and 1 to 15 parts by mass of one or more of a Si-containing compound, an Al-containing compound, a B-containing compound, a Ti-containing compound, a Na-containing compound, a Cu-containing compound, and an As-containing compound.
[0047] In some preferred embodiments, in the lead bismuth tellurium glass powder, the content of the Pb-containing compound is preferably 25 parts by mass, 27 parts by mass, 30 parts by mass, 32 parts by mass, 35 parts by mass, etc. The content of the Bi-containing compound is preferably 13 parts by mass, 15 parts by mass, 20 parts by mass, 22 parts by mass, 25 parts by mass, etc. The content of the Te-containing compound is preferably 25 parts by mass, 30 parts by mass, 35 parts by mass, 40 parts by mass, 45 parts by mass, etc. The content of other components (one or more of the Si-containing compound, the Al-containing compound, the B-containing compound, the Ti-containing compound, the Na-containing compound, the Cu-containing compound, and the As-containing compound) is preferably 1 part by mass, 3 parts by mass, 5 parts by mass, 10 parts by mass, 15 parts by mass, etc.
[0048] In the glass powder of this embodiment, the melting point of the entire glass powder is reduced to 300-450°C by compounding the bismuth-containing compound and the tellurium-containing compound, so that the wettability of the prepared silver paste on the surface of the solar cell silicon wafer at the corresponding sintering temperature can be improved, thereby improving the silver melting capacity; in addition, the addition of the tellurium-containing compound can also reduce the softening point of the glass system, increase the contact gain at the Ag / Si alloy interface, and reduce the contact resistance and line resistance of the silver electrode.
[0049] Furthermore, the organic binder includes: 2 to 10 parts by mass of an aqueous resin, 70 to 90 parts by mass of a solvent, and 1 to 3 parts by mass of a dispersant.
[0050] In some preferred embodiments, the content of the aqueous resin is preferably 2 parts by mass, 5 parts by mass, 8 parts by mass, 10 parts by mass, etc., and the aqueous resin may preferably be one or more of ethyl cellulose, acrylic resin, PVB resin, epoxy resin, and rosin resin. Of course, in other preferred embodiments, other aqueous resins may also be selected, which are not specifically limited here.
[0051] In other preferred embodiments, the content of the solvent is preferably 70 parts by mass, 75 parts by mass, 80 parts by mass, 85 parts by mass, 90 parts by mass, etc., and the solvent may preferably be one or more of pineol, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, and glycerol.
[0052] In other preferred embodiments, the content of the dispersant is preferably 1 part by mass, 2 parts by mass, 3 parts by mass, etc., and the dispersant may preferably be one or more of stearic acid, polyether, unsaturated fatty acid (e.g., polyacrylate), and phosphate ester. Of course, in other preferred embodiments, other dispersants may also be selected, which are not specifically limited here.
[0053] In this embodiment, the organic binder formed based on the above components helps to improve the dispersibility of the slurry, and at the same time enables the slurry after auxiliary sintering to form a more uniform and dense sintered film on the surface of the battery silicon wafer, thereby achieving better conductivity.
[0054] like Figure 1 As shown, another aspect of the present disclosure provides a method S100 for preparing the silver paste for the back side of the thin poly battery sheet as described above, comprising the following specific steps S110 to S130:
[0055] S110, mixing the primary spherical silver powder, the secondary spherical silver powder, the lead bismuth telluride glass and the organic binder to obtain a mixed material.
[0056] Specifically, the primary spherical silver powder, the secondary spherical silver powder, the lead bismuth telluride glass and the organic binder are accurately weighed on an electronic balance and mixed to obtain a mixed material.
[0057] In some preferred embodiments, the content of the primary spherical silver powder is preferably 85-89 parts by mass, the content of the secondary spherical silver powder is preferably 1-5 parts by mass, the content of the lead bismuth telluride glass powder is preferably 1.5-2 parts by mass, and the content of the organic binder is preferably 6-11 parts by mass.
[0058] In other preferred embodiments, the D50 particle size of the main spherical silver powder is 1.5-2 μm, and the specific surface area of the main spherical silver powder is 0.4-0.8 m 2 / g, tap density is 5~8g / cm 3 .
[0059] In other preferred embodiments, the D50 particle size of the para-spherical silver powder is 2.5-3 μm, and the specific surface area of the para-spherical silver powder is 0.1-0.3 m 2 / g, tap density is 5~8g / cm 3 .
[0060] In other preferred embodiments, the lead bismuth telluride glass powder includes: 25 to 35 parts by mass of a Pb-containing compound; 13 to 25 parts by mass of a Bi-containing compound; 25 to 45 parts by mass of a Te-containing compound; and 1 to 15 parts by mass of one or more of a Si-containing compound, an Al-containing compound, a B-containing compound, a Ti-containing compound, a Na-containing compound, a Cu-containing compound, and an As-containing compound.
[0061] In other preferred embodiments, the organic binder includes: 2 to 10 parts by mass of an aqueous resin; 70 to 90 parts by mass of a solvent; and 1 to 3 parts by mass of a dispersant.
[0062] As a further preferred embodiment, the water-based resin is one or more of ethyl cellulose, acrylic resin, PVB resin, epoxy resin, and rosin resin. The solvent is one or more of terpineol, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, and glycerol. The dispersant is one or more of stearic acid, polyether, unsaturated fatty acid, and phosphate.
[0063] S120, centrifuging the mixed material to obtain an intermediate slurry.
[0064] Specifically, the mixed material obtained in step S110 is placed in a centrifuge and centrifuged twice to preliminarily mix the materials. In each centrifugation, the speed is 500-600 rpm, the time is 2-7 minutes, and the materials are manually stirred after one centrifugation.
[0065] S130, using a three-roll grinder to mix the intermediate slurry evenly to obtain a high-activity back silver paste.
[0066] Specifically, the intermediate slurry obtained by centrifugation in step S120 is fully mixed and uniformly processed by a three-roll grinder, and the rollers are rolled repeatedly for four times. In the four rolling processes, the spacing 1 and spacing 2 of the three rollers are set to 50μm, 30μm; 30μm, 15μm; 15μm, 8μm; 15μm, 8μm, respectively, and the rotation speed is set to 100-300rpm. The final product fineness is less than 15μm, and the N-type thin poly layer TOPCon back side sub-gate conductive silver paste is obtained.
[0067] The preparation method of this embodiment is simple. The secondary spherical silver powder with a larger powder particle size is doped with the main spherical silver powder in a certain proportion to prepare a high-activity back silver paste. The prepared silver paste has a lower sintering temperature and higher sintering activity, which ensures good contact with the silicon substrate and can match the TOPCon field's battery cell thinning cost reduction strategy.
[0068] In another aspect of the present disclosure, an N-type TOPCon battery is provided. The back side of the N-type TOPCon battery has a grid line, and the material of the grid line is the high-activity back side silver paste described above.
[0069] The slurry of this embodiment can be used to prepare TOPCon cells with a Poly layer thickness of no more than 100nm. The slurry is printed or coated on the cell silicon wafer and undergoes a sintering or curing process to form electrode grid lines responsible for current collection and transmission. The slurry can fundamentally solve the problem of requiring more silicon material costs for TOPCon cells when producing the same power requirements.
[0070] The following will further illustrate the high-activity back silver paste and performance suitable for thin poly solar cells in conjunction with specific examples:
[0071] Example 1
[0072] The method for preparing the high-activity back silver paste suitable for thin poly solar cells in this example includes the following steps:
[0073] S1. Accurately weigh 87 parts by mass of primary spherical silver powder, 3 parts by mass of secondary spherical silver powder, 2 parts by mass of lead bismuth telluride glass powder, and 8 parts by mass of an organic binder on an electronic balance and mix them.
[0074] The main spherical silver powder has a D50 particle size of 1.6 μm and a specific surface area of 0.75 m 2 / g, tap density 6.9g / cm 3 The D50 particle size of the paraspherical silver powder is 2.5 μm, and the specific surface area is 0.3 m 2 / g, tap density 6.8g / cm 3 .
[0075] Among them, the components of the lead bismuth telluride glass powder include, in parts by mass: 32 parts by mass of Pb oxide; 20 parts by mass of Bi oxide; 38 parts by mass of Te oxide; 4 parts by mass of Cu oxide; 3 parts by mass of Na oxide; and 3 parts by mass of Al oxide.
[0076] The organic binder includes the following components in parts by mass: 8 parts by mass of water-based resin; 89 parts by mass of solvent; and 3 parts by mass of dispersant. The water-based resin is ethyl cellulose, acrylic resin, PVB resin, epoxy resin, and rosin resin in a mass ratio of 2:2:8:5:7; the solvent is diethylene glycol butyl ether and diethylene glycol butyl ether acetate in a mass ratio of 1.5:1; and the dispersant is polyether, polyacrylate, and phosphate in a mass ratio of 1.5:1:1.1.
[0077] S2. The blended material is placed in a centrifuge and centrifuged twice to preliminarily mix the material; wherein the centrifugal speed is 550 rpm, the centrifugal time is 5 min, and the material is manually stirred after one centrifugation.
[0078] S3. Use a three-roller grinder to fully mix the slurry obtained by centrifugation, set the three roller spacing 1 and spacing 2 to 50μm, 30μm; 30μm, 15μm; 15μm, 8μm; 15μm, 8μm, respectively, set the speed to 150rpm, repeat the rolling four times, and the final product fineness is less than 15μm, thus obtaining N-type thin poly layer TOPCon back side sub-gate conductive silver paste.
[0079] Furthermore, in this embodiment 1, the resistance-related properties, saturated current density, open circuit voltage, etc. of the slurry were tested, wherein:
[0080] 1. Resistance related performance test:
[0081] Contact resistance test: Use a contact resistance tester to perform linear fitting through the TLM method, and reverse the square resistance to obtain the ohmic contact resistance;
[0082] Line width, line height, and cross-sectional area are measured by a 3D profilometer, and the data can be automatically measured after the sample is placed;
[0083] 2. Saturation current density (J0) and open circuit voltage test:
[0084] Test items: open circuit voltage Voc, saturation current density;
[0085] Test instrument: WCT-120 instrument measures minority carrier lifetime and obtains composite size through linear fitting Test conditions: STC, 25℃, 1000W / m 2 .
[0086] Furthermore, the test results are shown in Table 1, the contact resistance is 0.44Ω, and the saturation current density is 80fA·cm -2 , the open circuit voltage is 733.8mV, and the photoelectric conversion efficiency is 25.02%.
[0087] Example 2
[0088] The preparation method of this example is the same as that of Example 1, except that the components and contents are different, as follows:
[0089] 87 parts by mass of main spherical silver powder, 3 parts by mass of secondary spherical silver powder, 2 parts by mass of lead bismuth telluride glass powder, and 8 parts by mass of organic binder; wherein the D50 particle size of the main spherical silver powder is 1.7 μm, and the specific surface area is 0.69 m 2 / g, tap density 6.3g / cm 3 The D50 particle size of the paraspherical silver powder is 2.6 μm, and the specific surface area is 0.3 m 2 / g, tap density 6.6g / cm 3 Except for the particle size of the silver powder and other parameters, the other components are the same as those in Example 1.
[0090] Furthermore, in this Example 2, the same method as that in Example 1 was used to test the resistance-related properties, saturation current density, open circuit voltage, etc. of the slurry.
[0091] Furthermore, the test results are shown in Table 1. The contact resistance is 0.26Ω and the saturation current density is 56fA·cm -2 , the open circuit voltage is 734.3mV, and the photoelectric conversion efficiency is 25.24%.
[0092] Example 3
[0093] The preparation method of this example is the same as that of Example 1, except that the components and contents are different, as follows:
[0094] 87 parts by mass of main spherical silver powder, 3 parts by mass of secondary spherical silver powder, 2 parts by mass of lead bismuth telluride glass powder, and 8 parts by mass of organic binder; wherein the D50 particle size of the main spherical silver powder is 1.78 μm, and the specific surface area is 0.65 m 2 / g, tap density 6.0g / cm 3 The D50 particle size of the paraspherical silver powder is 2.7 μm, and the specific surface area is 0.26 m 2 / g, tap density 6.1g / cm 3 Except for the particle size of the silver powder and other parameters, the other components are the same as those in Example 1.
[0095] Furthermore, in this Example 3, the same method as that in Example 1 was used to test the resistance-related properties, saturation current density, open circuit voltage, etc. of the slurry.
[0096] Furthermore, the test results are shown in Table 1. The contact resistance is 0.49Ω and the saturation current density is 92fA·cm -2 , the open circuit voltage is 733.6mV, and the photoelectric conversion efficiency is 25.98%.
[0097] Example 4
[0098] The preparation method of this example is the same as that of Example 1, except that the components and contents are different, as follows:
[0099] 87 parts by mass of main spherical silver powder, 3 parts by mass of secondary spherical silver powder, 2 parts by mass of lead bismuth telluride glass powder, and 8 parts by mass of organic binder; wherein the D50 particle size of the main spherical silver powder is 2 μm, and the specific surface area is 0.46 m 2 / g, tap density 5.9g / cm 3 The D50 particle size of the paraspherical silver powder is 3 μm, and the specific surface area is 0.81 m 2 / g, tap density 5.6g / cm 3 Except for the particle size of the silver powder and other parameters, the other components are the same as those in Example 1.
[0100] Furthermore, in this Example 4, the same method as that in Example 1 was used to test the resistance-related properties, saturation current density, open circuit voltage, etc. of the slurry.
[0101] Furthermore, the test results are shown in Table 1, the contact resistance is 0.52Ω, and the saturation current density is 76fA·cm -2 , the open circuit voltage is 733.4mV, and the photoelectric conversion efficiency is 24.88%.
[0102] Comparative Example 1
[0103] The preparation method of this example is the same as that of Example 1, except that the components and contents are different, as follows:
[0104] 90 parts by mass of main spherical silver powder, 2 parts by mass of lead bismuth telluride glass powder, and 8 parts by mass of organic binder. The main spherical silver powder has a D50 particle size of 1.6 μm and a specific surface area of 0.75 m 2 / g, tap density 6.9g / cm 3 Except for the type and content of silver powder, the other components are the same as those in Example 1.
[0105] Furthermore, in this comparative example 1, the resistance-related properties, saturation current density, open circuit voltage, etc. of the slurry were tested using the same method as in Example 1.
[0106] Furthermore, the test results are shown in Table 1. The contact resistance is 0.81Ω and the saturation current density is 102fA·cm -2 , the open circuit voltage is 733.1mV, and the photoelectric conversion efficiency is 24.79%.
[0107] Comparative Example 2
[0108] The preparation method of this example is the same as that of Example 1, except that the components and contents are different, as follows:
[0109] 87 parts by mass of main spherical silver powder, 3 parts by mass of secondary spherical silver powder, 2 parts by mass of lead bismuth telluride glass powder, and 8 parts by mass of organic binder. The main spherical silver powder has a D50 particle size of 1.1 μm and a specific surface area of 0.9 m 2 / g, tap density 8.9g / cm 3 The D50 particle size of the paraspherical silver powder is 2.2 μm, and the specific surface area is 0.43 m 2 / g, tap density 8.3g / cm 3 Except for the particle size of the silver powder and other parameters, the other components are the same as those in Example 1.
[0110] Furthermore, in this comparative example 2, the resistance-related properties, saturation current density, open circuit voltage, etc. of the slurry were tested using the same method as in Example 1.
[0111] Furthermore, the test results are shown in Table 1, the contact resistance is 0.77Ω, and the saturation current density is 111fA·cm -2 , the open circuit voltage is 733.1mV, and the photoelectric conversion efficiency is 24.82%.
[0112] Comparative Example 3
[0113] The preparation method of this example is the same as that of Example 1, except that the components and contents are different, as follows:
[0114] 87 parts by mass of primary spherical silver powder, 3 parts by mass of secondary spherical silver powder, 2 parts by mass of lead bismuth telluride glass powder, and 8 parts by mass of organic binder. The primary spherical silver powder has a D50 particle size of 2.5 μm and a specific surface area of 0.56 m 2 / g, tap density 5.5g / cm 3 The D50 particle size of the paraspherical silver powder is 8 μm and the specific surface area is 0.1 m 2 / g, tap density 4.5g / cm 3 Except for the particle size of the silver powder and other parameters, the other components are the same as those in Example 1.
[0115] Furthermore, in this comparative example 3, the resistance-related properties, saturation current density, open circuit voltage, etc. of the slurry were tested using the same method as in Example 1.
[0116] Furthermore, the test results are shown in Table 1. The contact resistance is 0.79Ω and the saturation current density is 126fA·cm -2 , the open circuit voltage is 733.4mV, and the photoelectric conversion efficiency is 24.75%.
[0117] Comparative Example 4
[0118] The preparation method of this example is the same as that of Example 1, except that the components and contents are different, as follows:
[0119] 87 parts by mass of primary spherical silver powder, 3 parts by mass of secondary spherical silver powder, 2 parts by mass of vanadium glass powder, and 8 parts by mass of organic binder. Except for the glass powder, the other components are the same as those in Example 1.
[0120] Furthermore, in this comparative example 4, the resistance-related properties, saturation current density, open circuit voltage, etc. of the slurry were tested using the same method as in Example 1.
[0121] Furthermore, the test results are shown in Table 1, the contact resistance is 1.05Ω, and the saturation current density is 174fA·cm -2 , the open circuit voltage is 732.5mV, and the photoelectric conversion efficiency is 24.12%.
[0122] Table 1 Performance of backside paste of each embodiment and comparative example
[0123]
[0124] In summary, in combination with Examples 1-4, compared with Comparative Example 1, it can be seen that when the silver powder only includes the main spherical silver powder, the contact resistance and saturation current density of the slurry are increased, and the open circuit voltage and photoelectric conversion efficiency are reduced, which shows that doping large-particle silver powder in small-particle silver powder can reduce resistance, increase conductivity, etc. Compared with Comparative Examples 2 and 3, it can be seen that when the particle size of the silver powder is too small or too large, it will also cause the contact resistance and saturation current density to increase, and the open circuit voltage and photoelectric conversion efficiency to decrease. Compared with Comparative Example 4, it can be seen that when the glass powder is changed, the contact resistance and current density are further increased, and the open circuit voltage and photoelectric conversion efficiency are further reduced, which shows that the lead bismuth telluride glass powder used in the present disclosure can reduce the line resistance of the contact silver electrode, etc.
[0125] The present disclosure proposes a preparation method and specific application of a high-activity back silver paste suitable for thin poly solar cells, which has the following beneficial effects compared with the prior art:
[0126] First, by doping the secondary spherical silver powder with larger particle size with the main spherical silver powder in a certain proportion, a high-activity back silver paste is prepared, which can match the cost reduction strategy of thinning battery cells in the TOPCon field. It can fundamentally solve the problem that TOPCon batteries require more silicon material costs when producing the same power requirements.
[0127] Second, the prepared slurry reduces the higher sintering temperature required to be reached during the cell metallization process during the sintering process. The reduction in sintering temperature minimizes the carrier recombination rate and improves the carrier mobility, which to a certain extent helps to avoid the problem of reduced cell efficiency caused by thermal deformation of the substrate single crystal silicon wafer during high-temperature sintering under the cell thinning strategy.
[0128] Third, the slurry has a higher sintering activity. After sintering, the slurry forms a more uniform and dense sintering film on the surface of the battery silicon wafer.
[0129] Fourth, by utilizing the complementary filling synergy of the main and auxiliary silver powders with significantly different particle sizes, combined with the glass phase with a high softening point, it is possible to ensure good contact between metal and metal, and between metal and battery silicon wafers on the poly-layer thinned battery cells at the lowest possible sintering temperature.
[0130] Fifth, by doping with large-particle silver powder, the high sintering temperature required for battery metallization can be effectively reduced while maintaining good contact. Under the same background conditions, the smaller the contact resistance, the better the circuit conductivity and the higher the efficiency of the battery cell.
[0131] Sixth, the coordination of small-particle main silver powder with organic components and inorganic components can reduce the voltage loss of the battery cell caused by low temperature as much as possible, thereby ensuring that the overall efficiency of the thinned battery cell can be the same as or even better than that of the conventional battery cell.
[0132] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present disclosure, but the present disclosure is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and substance of the present disclosure, and these modifications and improvements are also considered to be within the scope of protection of the present disclosure.
Claims
1. A silver paste suitable for the back side of thin poly battery cells, characterized in that: The back silver paste comprises: 85-89 parts by mass of primary spherical silver powder; 1 to 5 parts by weight of para-spherical silver powder; 1.5-2 parts by mass of lead bismuth telluride glass powder; 6 to 11 parts by mass of an organic binder; wherein, The D50 particle size of the primary spherical silver powder is 1.5 to 2 μm, and the D50 particle size of the secondary spherical silver powder is 2.5 to 3 μm.
2. The back silver paste according to claim 1, characterized in that: The specific surface area of the main spherical silver powder is 0.4 to 0.8 m 2 / g, tap density is 5~8g / cm 3 .
3. The back silver paste according to claim 1, characterized in that: The specific surface area of the paraspherical silver powder is 0.1 to 0.3 m 2 / g, tap density is 5~8g / cm 3 .
4. The back silver paste according to claim 1, characterized in that: The lead bismuth telluride glass powder comprises: 25 to 35 parts by mass of a Pb-containing compound; 13 to 25 parts by mass of a Bi-containing compound; 25 to 45 parts by mass of a Te-containing compound; 1 to 15 parts by mass of one or more of Si-containing compounds, Al-containing compounds, B-containing compounds, Ti-containing compounds, Na-containing compounds, Cu-containing compounds, and As-containing compounds.
5. The back silver paste according to claim 1, characterized in that: The organic binder comprises: 2 to 10 parts by weight of water-based resin; 70 to 90 parts by weight of a solvent; 1 to 3 parts by mass of a dispersant.
6. The back silver paste according to claim 5, characterized in that: The water-based resin is one or more of ethyl cellulose, acrylic resin, PVB resin, epoxy resin, and rosin resin; and / or, The solvent is one or more of terpineol, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, and glycerol; and / or, The dispersant is one or more of stearic acid, polyether, unsaturated fatty acid and phosphate.
7. A method for preparing the back silver paste suitable for thin poly battery cells as claimed in any one of claims 1 to 6, characterized in that: The method comprises: The main spherical silver powder, the auxiliary spherical silver powder, the lead bismuth telluride glass and the organic binder are mixed to obtain a mixed material; Centrifuging the mixed material to obtain an intermediate slurry; The intermediate slurry was mixed evenly using a three-roll grinder to obtain a back silver paste.
8. The method according to claim 7, characterized in that The centrifugal treatment is performed at a speed of 500-600 rpm for 2-7 min; and / or The intermediate slurry was rolled four times using a three-roll mill, and the rotation speed of the three-roll mill was 100-300 rpm during each rolling process.
9. The method according to claim 7, characterized in that: The fineness of the back silver paste is less than 15 μm.
10. An N-type TOPCon battery, characterized in that: The back side of the N-type TOPCon battery has a grid line, and the material of the grid line is the back side silver paste according to any one of claims 1 to 6.